2010
DOI: 10.1002/mc.20652
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of MMP‐2 through the p38 MAPK‐NF‐κB‐dependent pathway by aloe‐emodin leads to inhibition of nasopharyngeal carcinoma cell invasion

Abstract: Aloe-emodin (AE), extracted from the rhizome of Rheum palmatum, has an anti-proliferative effect on different human cancer cell lines. Nonetheless, the underlying mechanism by which AE inhibits nasopharyngeal carcinoma (NPC) cell invasion is still unclear. The results of this study show that treatment of NPC cells with growth suppressive concentrations of AE caused cell cycle arrest at the S-G(2)/M phase. Coimmunoprecipitation and small interfering RNA (siRNA) studies demonstrated that AE-induced cell cycle ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 38 publications
3
70
0
Order By: Relevance
“…These results indicate that caspase-8-mediated activation of the mitochondrial death pathway plays a critical role in 60 M AE-induced apoptosis of NPC cells (178). A more recent investigation has revealed that 40 M AE significantly inhibits NPC cell growth through cell cycle arrest at the S-G 2 /M phase, which is associated with increased levels of cyclin B1 bound to Cdk1 but not the apoptotic process (179). Gene silencing of MMP-2 mediated by siRNA inhibits NPC cell invasion, thereby demonstrating the involvement of MMP-2 in the NPC invasion process (179).…”
Section: The Inhibitory Mechanisms Of Natural Compounds Against Npc Smentioning
confidence: 79%
See 3 more Smart Citations
“…These results indicate that caspase-8-mediated activation of the mitochondrial death pathway plays a critical role in 60 M AE-induced apoptosis of NPC cells (178). A more recent investigation has revealed that 40 M AE significantly inhibits NPC cell growth through cell cycle arrest at the S-G 2 /M phase, which is associated with increased levels of cyclin B1 bound to Cdk1 but not the apoptotic process (179). Gene silencing of MMP-2 mediated by siRNA inhibits NPC cell invasion, thereby demonstrating the involvement of MMP-2 in the NPC invasion process (179).…”
Section: The Inhibitory Mechanisms Of Natural Compounds Against Npc Smentioning
confidence: 79%
“…Consistent with the data presented by Lee et al (156), an increase in intracellular ROS levels was observed when apoptosis was induced in NPC cells using 60 M AE (178). However, apoptosis, DNA damage, and increases in ROS levels were not detected in the same cells treated with 40 M AE, therefore suggesting that different concentrations of AE could differentially modulate the expression of cellular genes that are involved in cell growth, apoptosis, and cell invasion in different types of cancer cells (179).…”
Section: The Inhibitory Mechanisms Of Natural Compounds Against Npc Smentioning
confidence: 94%
See 2 more Smart Citations
“…Lee et al, 2008). The promoter region of MMP-2 contains various cis-acting elements, including potential binding sites for the transcription factors nuclear factor-kappa B (NF-κB), activator protein-1 (AP-1), and stimulatory protein-1 (SP-1) (Lin et al, 2010). NFkB is critically involved in tumor progression through transcriptional regulation of invasion related factors, such as MMP-2/MM-9, uPA and VEGF (Shibata et al, 2002;Yang et al, 2011).…”
Section: A Camphorata Down-regulates Invasion and Metastasismentioning
confidence: 99%